The Effect of Using Katuk Leaves (Sauropus Androgynus (L) Merr) As A Substitute for ZA (Ammonium Sulfate) on the Yield, Thickness, Color, Texture, and Organoleptic of Nata De Whey - Fanny Virya Akni; Sri Melia; Indri Juliyarsi (Journal of Nutrition Science, 2024)
Utilization of cheese waste, namely whey, is one alternative to increase the added value of whey by processing it into nata de whey. This study aims to determine the effect of using Katuk leaves (Sauropus androgynus (L) Merr) as a substitute for ZA (Ammonium Sulfate) on the yield, thickness, color, texture, and organoleptic of Nata de whey.  This study used 8 liters of whey and Katuk leaves (Sauropus androgynus (L) Merr) as much as 600 g.  The experimental design used in this study, namely the Randomized Block Design (RBD) with four treatments and five repetitions.  The treatment in this study was A = 0.5% ZA, Katuk leaves (B = 5%, C = 10%, and D = 15%). The observed variables were yield, thickness, color, texture, and organoleptic.  The results showed that the treatment differed significantly (P<0.05) in yield, thickness, color, texture, and organoleptic.  The best treatment result is treatment B with a yield value of 91.94%, thickness of 7.77 mm, lightness (L*) 59.17, greenness (a*) -4.16, yellowness (b*) 7.52, texture 5.25 N/cm2, organoleptic color 3.90, scent 3.58, taste 3.82, texture 3.78.